Forming God : divine anthropomorphism in the Pentateuch - Knafl, Anne Katherine (Siphrut, 2014)
This volume examines divine anthropomorphism in the Hebrew Bible, a study characterized by disagreement and contradiction. Discussions of anthropomorphism in the Hebrew Bible are typically found in three areas of inquiry: ancient Israelite religion, as reflected by the compositions of the Pentateuch ; comparisons with ancient Near Eastern religions ; and comparison with ancient translation and interpretation of the Hebrew Bible. Contradictory arguments exist, both within each area of study and between them, about the intent of biblical writers, with respect to a theology of anthropomorphism. In this work, Knafl asserts that biblical studies has reached this impasse, largely due to its approach to the study of the phenomenon. The prevailing method has been to study divine anthropomorphism within an assumed framework of polemic and by associating it with a theological system. By contrast, Knafl analyzes divine anthropomorphism as a literary-contextual phenomenon and seeks to build a typology, from which secondary arguments regarding theology or history of religion may be built. This typology will provide scholars of biblical studies, history of religion, and (systematic) theology with a means of evaluating divine anthropomorphisms and their relation to human-divine interactions, as a biblical phenomenon.